Randomized controlled trial of seminar‐based training on accurate and general implementation of practical functional assessments. Issue 4 (24th May 2021) - Whelan, Cory J.; Hanley, Gregory P.; Landa, Robin; Sullivan, Emily; LaCroix, Kara; Metras, Rachel
Abstract : General and long‐term outcomes of functional analysis training have not yet been reported. Within a randomized control trial, we trained 18 behavior analytic practitioners to interview caregivers, design and then conduct a personalized analysis as a part of a practical functional assessment (PFA). Participants were randomly assigned to groups, and those who experienced the seminar prior to conducting PFA with a confederate demonstrated more component skills than those who were provided the same materials but did not experience the seminar (mean scores: 87%, 36% respectively). Participants who experienced the seminar considered the training valuable and reported greater confidence in their ability to achieve control in an analysis. Several participants then conducted a PFA with a client who engaged in SPB. Results showed that skills transferred to these authentic applications. Results suggest that a seminar‐based training can increase practitioners' ability to functionally analyze problem behavior and leads to subsequent analytic activity.